Video game performance analysis on selected operating systems - Agata Wrześniewska; Maria Skublewska-Paszkowska (Journal of Computer Sciences Institute)
The video game industry is currently one of the most dominant in IT. Unfortunately, developers rarely focus on maintaining older games, which often leads to the inability to launch them on newer systems. The aim of the paper is the video game performance analysis on selected operating systems. The analysis was performed on the first three installments of The Sims series, published in the first decade of the 21st century, on a computer with Windows XP as the operating system and another with Windows 10 as the operating system. For the performance analysis three hardware monitoring programs were used: Open Hardware Monitor, MSI Afterburner and Windows Performance Monitor. In addition, all tested games were compared visually in order to determine whether their appearance and available graphic options are the same on both systems. Results analysis have shown, that despite lower system load in all games on the computer with Windows 10 there are some graphical anomalies not present on the older operating system.